The virus–host interface: Molecular interactions of Alphacoronavirus‐1 variants from wild and domestic hosts with mammalian aminopeptidase N. Issue 11 (3rd May 2021) - Olarte‐Castillo, Ximena A.; dos Remédios, Joana F.; Heeger, Felix; Hofer, Heribert; Karl, Stephan; Greenwood, Alex D.; East, Marion L.
Abstract: The Alphacoronavirus ‐ 1 species include viruses that infect numerous mammalian species. To better understand the wide host range of these viruses, better knowledge on the molecular determinants of virus–host cell entry mechanisms in wildlife hosts is essential. We investigated Alphacoronavirus ‐ 1 infection in carnivores using long‐term data on Serengeti spotted hyenas ( Crocuta crocuta ) and molecular analyses guided by the tertiary structure of the viral spike (S) attachment protein's interface with the host receptor aminopeptidase N (APN). We sequenced the complete 3′‐end region of the genome of nine variants from wild African carnivores, plus the APN gene of 15 wild carnivore species. Our results revealed two outbreaks of Alphacoronavirus ‐ 1 infection in spotted hyenas associated with genetically distinct canine coronavirus type II (CCoVII) variants. Within the receptor binding domain (RBD) of the S gene the residues that directly bind to the APN receptor were conserved in all variants studied, even those infecting phylogenetically diverse host taxa. We identified a variable region within RBD located next to a region that directly interacts with the APN receptor. Two residues within this variable region were under positive selection in hyena variants, indicating that both sites were associated with adaptation of CCoVII to spotted hyena APN. Analysis of APN sequences revealed that most residues that interact with the S protein are conserved in wild carnivores, whereas some adjacent residues are highly variable. Of the variable residues, four that are critical for virus–host binding were under positive selection and may modulate the efficiency of virus attachment to carnivore APN.